“ANÁLISIS DE SINIESTRALIDAD EN LOS RAMOS DE VIDA, VEHÍCULOS Y TRANSPORTE DEL SECTOR ASEGURADOR EN GUAYAQUIL, - Avalos Flores, Katherine Zulay (2016)
The dynamism of the insurance market depends on several elements that intervene as drivers or conditioners. For insurance companies one of the main elements to take into consideration is the accident rate, which allows the institution to assess the strengths and weaknesses of its potential customers, in order to give the most appropriate rating depending on the type of bond that is requested. The present investigation details the importance of insurance companies in the market and explains the operations of the life, vehicle and transport sectors in Guayaquil. In addition, the hypothesis of the study was to demonstrate the increase in the level of demand due to an increase in the loss ratio of the mentioned branches. The general purpose of the investigation was to know the factors that determine the direction of the insurance. The research was exploratory in order to identify potential relationships between the analyzed variables. Finally, it was determined that there is no risk prevention culture in Guayaquil and there is no increase in demand in the insurance market caused by an increase in the number of accidents.